WOLLSTONECRAFT AND FRIEDANS THEORIES HIGHLIGHT THE WOMEN STRUGGLES IN JULIUS CAESAR - Ekawati Marhaenny Dukut; Farhana Malik (Soegijapranata Catholic University, 2013)
For centuries, women have been struggling to establish their place in the society and fight for their rights as becoming an equal to men. This article, presents an analysis on the female characters - Portia and Calpurnia of Rome, in Julius Caesar. The play was written by William Shakespeare who based his story on the historical events of Ancient Rome. Making use of Wollstonecraft and Friedans theories, this article aims at examining to what extent the struggles of women are reflected and presented in the play. The struggles of the female characters are intrinsically concerned with the play and extrinsically relates to the condition of women in Ancient Rome. Upon analyzing, it becomes clear that Roman women had less rights and privileges than men and were considered inferior to men. Women in Roman were seen as weak, feeble and unworthy. Although feminism is not even heard of in Shakespeares time, through studying Wollstonecraft and Friedans theories, Portia and Calpurnias struggle can be considered as the springing of feminists actions.